ANALISIS KETAATAN KARYAWAN DALAM PEMERIKSAAN KESEHATAN BERKALA DI RUMAH SAKIT PKU MUHAMMADIYAH KOTA YOGYAKARTA - Salhah, Afridah; Suwarni, Agus; Hariyono, Widodo (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2011)
Background: The hospital is one workplace where there is staff, patients, visitors, medical devices and non-medical, so in the hospital there are a variety of exposures, among others, chemical, biological, ergonomics. Employees at the hospital is a potential resource that must be nurtured to become productive and quality. But apparently in carrying out daily sociality services especially in the work environment, employees are more exposed to the various factors that may cause negative impact and affect their health status. Employees in hospitals vary greatly in terms of type and number in executing its duties is always associated with a variety of potential hazards if not properly and correctly anticipated to have a negative impact on safety and health, which in turn can affect the productivity of work. Low labor productivity will also have an impact on health services provided by the hospital. The implementation of occupational safety and health program (K3) in the hospital is required to prevent various hazards that may cause health effects. However, the implementation of K3 in particular areas of work on employee health in RS PKU Muhammadiyah Yogyakarta has not fully run optimally, citing the cost is relatively expensive. Method: This study was an observational study that was descriptive qualitative located in RS PKU Muhammadiyah Yogyakarta. The subjects consisted of Chairman PK3, PK3 Secretary, and 50 permanent employees in RS PKU Muhammadiyah Yogyakarta. Results: Based on the research of 52 employees, obtained results showed that the level of employee compliance in following the health checks can be quite good even as many as 65%. Conclusion: Factors inhibiting the implementation of occupational health in RS PKU Muhammadiyah Yogyakarta is the lack of socialization from the hospital to its employees, employee behavior, and no sanctions for employees who do not want to follow the program. While the reasons for employees to check their health on a regular basis is self-protection, and to know his health. Compliance level employees in the following periodic medical examinations in hospitals PKU Muhammadiyah Yogyakarta good enough. Level of occupational health services in RSU PKU Muhammadiyah Yogyakarta good enough. Keywords: Analyze, Employees Compliance, the Periodic Health Examination